A Hypothetical Exploration of Survival, Colonisation and Interplanetary Relations Around the planet Mars - Reid, Caroline (Centre for Film and Media Studies, 2019)
Three novellas exploring the short and long-term implications of Martian colonisation and an explication. The first part examines the necessity of a robust and mentally-fit crew along with the relationships between corporatism. The second, which happens a century later, explores the health effects of long-term living on Mars along with the Earth disconnect by Martian-born humans. In the third part, another century later, the long-term strains of sustaining such a project are examined on Earth and how Martians are used as scapegoats. The explication describes the scientific motivations behind some aspects of the novel, including how the conditions of Mars necessitates certain survival protocols.